Fracture Surface of OPEFB Fiber Reinforced Polymer Composites-Polymeric Foam Sandwich Panels under Static Loading Conditions - Badri, Muftil; Arief, Dodi Sofyan; Johanes, Erik Sitio; Rahmat, Ridho Zarli (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2017)
The fracture surface of oil palm empty fruit bunch (OPEFB) reinforced polymer composites sandwich panels depends on different fibers treatment was experimentally investigated under static loading conditions. The static uniaxial tensile and flexural loading for three treatment modes on OPEFB fibers was implemented using servo hydraulic material testing machine. The microstructure was observed using SEM observation in order to better understand damage mechanism during the stress of polyester phase. SEM observation on fracture surface can provide important information for research and development as well as fracture analysis. It was found that fracture modes were considerably different for these composites. OPEFB fibers was soaked with 5% NaOH solution for 2 hours are not removed from the matrix composite. It means the interface bonds of OPEFB fibers can be controlled against the polymer matrix. Damage to polymer matrix interface and OPEFB fiber are boiled with water at temperatures of 50º C to 80º C for 30 minutes due to flexural test.